2002
DOI: 10.1029/2002gl015816
|View full text |Cite
|
Sign up to set email alerts
|

A new method for the quantitative identification of the composition, size and density of stratospheric aerosols from high resolution IR satellite measurements

Abstract: We describe a new method for the rapid and quantitative determination of the composition, size and density of atmospheric aerosols from broadband high resolution IR spectra recorded by remote sensing instruments. This method uses a novel technique for the separation of the aerosol spectrum from that of the gas phase. It is fast enough to permit the analysis of high resolution IR satellite measurements in real time, yielding aerosol composition, size distribution and volume density. The method is applied to spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Aerosols particles are assumed to have a radius of less than 1 mm and a composition of 80 wt. % H 2 SO 4 , as reported by Zasetsky et al [2002]. For such small particles and slow reactions, the reacto-diffusive length [Hanson et al, 1994] of acetaldehyde in the particles (distance over which reaction is taking place) is about 10 À2 cm, much larger than the particles radius.…”
Section: Atmospheric Implicationsmentioning
confidence: 73%
See 1 more Smart Citation
“…Aerosols particles are assumed to have a radius of less than 1 mm and a composition of 80 wt. % H 2 SO 4 , as reported by Zasetsky et al [2002]. For such small particles and slow reactions, the reacto-diffusive length [Hanson et al, 1994] of acetaldehyde in the particles (distance over which reaction is taking place) is about 10 À2 cm, much larger than the particles radius.…”
Section: Atmospheric Implicationsmentioning
confidence: 73%
“…[2] Observations have now well established that gasphase carbonyl compounds and aerosols containing sulfuric acid are simultaneously present throughout the atmosphere (see, for example, Singh et al [2001] for vertical profiles of carbonyl compounds, and Zasetsky et al [2002] for vertical profiles of sulfuric acid aerosols). Recent laboratory studies have shown that under atmospheric conditions gas-phase carbonyl compounds are irreversibly taken up by acidic solutions such as sulfuric acid [Duncan et al, 1998[Duncan et al, , 1999Kane et al, 1999;Michelsen et al, 2004; W. Esteve and B. Noziere, Uptake and reaction kinetics of acetone, 2-butanone, and 2,4-pentanedione in sulfuric acid solutions, submitted to Journal of Physical Chemistry, 2004, hereinafter referred to as Esteve and Noziere, submitted manuscript, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…In the inversion procedure, we first process the observed spectrum using a wavelet filter and a weight function based on smoothness criteria. Then the retrieval is carried out using a constrained linear least squares procedure involving the comparison of the smoothed, weighted spectrum with a library of 96 monodisperse reference spectra covering the radius range of interest [Zasetsky et al, 2002;Zasetsky et al, 2004aZasetsky et al, , 2004b. The condensed phase spectrum shown in Figure 1 is the combination of reference spectra that provides the best fit.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported details of the procedures we use to retrieve this information [Zasetsky et al, 2002;Zasetsky et al, 2004b] and have shown that these methods can provide significant detail on the size distributions for particles that are smaller than about 30 mm, while larger particles are identified only by their contribution to the extinction, since their spectra do not have identifying features that are unique to their sizes. The amount of information that we can retrieve using this method depends to some extent on the signal to noise of the observation and the amount of interference by gas phase components.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the ATMOS measurements to determine stratospheric aerosol composition, size, and density have also been reported by Zasetsky et al [2002]. Aimed at developing an extremely fast computational technique, this analysis applied a very different method than is used here for separating the gas and aerosol signatures.…”
Section: Introductionmentioning
confidence: 99%